2019
DOI: 10.1016/j.dadm.2018.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Brain and cognitive correlates of sleep fragmentation in elderly subjects with and without cognitive deficits

Abstract: Introduction Sleep disturbances are increasingly recognized as a risk factor for Alzheimer's disease. However, no study has assessed the relationships between objective sleep fragmentation (SF) and brain and cognitive integrity across different cognitive stages, from cognitively unimpaired elderly subjects to patients with subjective cognitive decline and/or mild cognitive impairment. Methods 30 cognitively unimpaired elderly participants and 36 patients with subjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 53 publications
5
42
1
Order By: Relevance
“…Regarding possible mechanistic links between these alterations and poor sleep quality, it has been hypothesized that orbitofrontal cortex abnormalities may predispose to insomnia due to altered sensing of the optimal temperature for sleep [14,59,60]. As far as we are concerned, lower thalamic volume has not been previously reported in patients with insomnia, although it has been associated with increased sleep fragmentation variability in cognitively unimpaired elderly subjects [61]. Thalamic involvement in sleep disturbances is biologically plausible, since regulation of wakefulness and sleep cycles largely relies on a neural network involving neurons in the brainstem, hypothalamus and basal forebrain that provides excitatory input to the thalami and cortical regions [62].…”
Section: Discussionmentioning
confidence: 85%
“…Regarding possible mechanistic links between these alterations and poor sleep quality, it has been hypothesized that orbitofrontal cortex abnormalities may predispose to insomnia due to altered sensing of the optimal temperature for sleep [14,59,60]. As far as we are concerned, lower thalamic volume has not been previously reported in patients with insomnia, although it has been associated with increased sleep fragmentation variability in cognitively unimpaired elderly subjects [61]. Thalamic involvement in sleep disturbances is biologically plausible, since regulation of wakefulness and sleep cycles largely relies on a neural network involving neurons in the brainstem, hypothalamus and basal forebrain that provides excitatory input to the thalami and cortical regions [62].…”
Section: Discussionmentioning
confidence: 85%
“…Finally, Florbetapir SUVR images were masked to exclude non-gray matter voxels. Normalized and scaled Florbetapir-PET images were used to extract an averaged index of cortical Aβ, using a predetermined neocortical mask (including the entire gray matter, except the cerebellum, occipital and sensory motor cortices, hippocampi, amygdala, and basal nuclei) [40]. Florbetapir-PET SUVR data were mainly used as a continuous variable in the analyses; for some analyses, however, they were also dichotomized as amyloid positive versus negative using a cutoff corresponding to the 99.9th percentile of SUVR distribution among cognitively unimpaired young adults aged < 40 years (n = 45) [41].…”
Section: Florbetapir (F 18 -Av45) Petmentioning
confidence: 99%
“…Regions of interest based approaches mainly targeted on frontal, temporal, hippocampal, and thalamic grey matter volume, considering the predominant implication of those regions in brain ageing trajectory but also in sleep-wake regulation or more specifically, in the generation and/or coupling of slow oscillations and sleep spindles. Of thirteen MRI studies including subcortical structures [8-13,15,32 ,33,40-42,43 ], only four reported a positive association between sleep-wake patterns and hippocampal [10,15,42] or thalamic volumes [10,41]. In contrast, all polysomnographic studies included in this Conceptual representation of (a) results from studies reporting an association between sleep-wake states and MRI-derived brain structure and (b) methodological considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Note that most studies have focused on sleep and its disturbances without considering it as a part of a 24-hour cycle. Of seven [40,41,42,43,44,45,47] studies using MRI and actigraphy, only four described rest-activity patterns [42,43 ,45,47] and most of them emphasized an association with white matter properties. Furthermore, postmortem studies provide evidence that actigraphic restactivity patterns are associated with degeneration of hypothalamic neurons implicated in circadian timing and sleep-wake regulation, regions not easily reachable with conventional MRI [37,39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation